2023
DOI: 10.1101/2023.04.09.536152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Boosting BDNF in muscle rescues impaired axonal transport in a mouse model of DI-CMTC peripheral neuropathy

Abstract: Charcot-Marie-Tooth disease (CMT) is a form of genetic peripheral neuropathy caused by mutations in many functionally diverse genes. The aminoacyl-tRNA synthetase (ARS) enzymes, which charge amino acids to partner tRNAs for protein synthesis, represent the largest protein family linked to CMT aetiology, suggestive of pathomechanistic commonalities. Dominant intermediate CMT type C (DI-CMTC) is caused byYARS1mutations driving a toxic gain-of-function in the encoded tyrosyl-tRNA synthetase (TyrRS), which is medi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 101 publications
(213 reference statements)
0
1
0
Order By: Relevance
“…It is tempting to speculate that locally activated ERK1/2 is able to hitchhike on SEs back to soma to switch on pro-survival programs. Our previous work showed that local muscle administration or viral overexpression of BDNF in muscles corrects axonal transport defects of SEs and pathological symptoms in peripheral neuropathy mouse models 73,92 .…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that locally activated ERK1/2 is able to hitchhike on SEs back to soma to switch on pro-survival programs. Our previous work showed that local muscle administration or viral overexpression of BDNF in muscles corrects axonal transport defects of SEs and pathological symptoms in peripheral neuropathy mouse models 73,92 .…”
Section: Discussionmentioning
confidence: 99%